2019
DOI: 10.1111/jdv.15312
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation exposure among Belgrade high school students: analysis of knowledge, attitudes and behaviour

Abstract: Background The incidence of melanoma has been increasing worldwide. Extended UV exposure during childhood or adolescence significantly increases the probability of skin cancer in adulthood. Objective The objective of this study was to analyse knowledge, attitudes and behaviour regarding exposure to natural and artificial UV radiation among Belgrade high school students. Methods The study was conducted using a questionnaire among 549 students of 3rd and 4th grade (17 and 18 years of age) in four Belgrade high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Studies from multiple countries surveying adolescents' lifestyle choices found high reported levels of smoking, alcohol consumption, tanning bed use, poor physical activity, and low awareness of healthy eating habits. [36][37][38][39][40] One study found adolescents in rural areas use less sun protection behaviors than in urban areas. 36 Similarly, half of the participants in this study reported they do not currently implement strategies to prevent cancer in their daily life, and few recognized which of their daily behaviors could reduce their risk of cancer.…”
Section: Knowledge and Behaviors Toward Cancermentioning
confidence: 99%
“…Studies from multiple countries surveying adolescents' lifestyle choices found high reported levels of smoking, alcohol consumption, tanning bed use, poor physical activity, and low awareness of healthy eating habits. [36][37][38][39][40] One study found adolescents in rural areas use less sun protection behaviors than in urban areas. 36 Similarly, half of the participants in this study reported they do not currently implement strategies to prevent cancer in their daily life, and few recognized which of their daily behaviors could reduce their risk of cancer.…”
Section: Knowledge and Behaviors Toward Cancermentioning
confidence: 99%
“…National studies have typically reported the prevalence of either outdoor tanning or tanning bed use, and only a limited number of studies included both aspects of UVexposure [12,13,[21][22][23][24]. This represents an important gap in our understanding because combining both is a high-risk UV-exposure behavior, which likely would increase skin cancer risk.…”
Section: Introductionmentioning
confidence: 99%